A Conceptual Multi-Agent Semantic Web Model of a self-Adaptive website for intelligent strategic marketing in learning institutions - Yusof A.; Mahmoud M.A.; Ahmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Commerce; Intelligent agents; Marketing; Robotics; Sales; Semantic Web; Social networking (online); Societies and institutions; Web Design; Websites; Conceptual model; Dynamic website; Generator systems; Grouping process; Rendering engine; Semantic web models; Semantics web; Strategic marketing; Multi agent systems